How to cheat at managing Microsoft Operations Manager 2005 - Piltzecker, Tony, 1975-; Cross, Michael, 1965- (Rockland, MA : Syngress, 2006)
Microsoft Operations Manager (MOM) is a network monitoring tool that provides enterprise-class event and performance management for Windows Server System technologies. MOM's event and performance management tools discover problems before system administrators would ever find them, thereby enabling administrators to lower their costs of operations and simplify management of their Windows Server System infrastructure. MOM can notify system administrators of overloaded processors, depleted memory, or failed network connections affecting their Windows servers long before these problems bother users. Microsoft Operations Manager (MOM) 2005 delivers open and scalable enterprise-class operational management by providing comprehensive event management, proactive monitoring and alerting, reporting and trend analysis, and system and application specific knowledge and tasks to improve the manageability of Windows Server System environments, including Windows, Exchange, SQL, IIS, Active Directory etc. * A users guide to Microsoft Operations Manager (MOM) enabling a cost reduction and simplification in managing your Windows Server System Infrastructure * Companion Web site for book offers dozens of customized scripts and tools for automating MOM 2005 and many other Windows Server products * There is no other compact resource like this for this core, Microsoft Server product.
Microsoft Operations Manager 2005 essentials -- Evaluating your environment -- Planning a MOM 2005 deployment -- Installing Microsoft MOM 2005 -- Understanding and deploying management packs -- Managing Microsoft Exchange -- Managing SQL Server 2000 -- Managing Microsoft Active Directory -- Managing Intel-based hardware -- Managing Linux, UNIX, and Solaris -- Connecting to other management platforms -- Planning for Microsoft System Center -- Troubleshooting MOM.
Includes index.
Keywords: Microsoft Operations Manager; Client/server computing; Electronic books